A Cross-sectional Study to Explore the Adverse Childhood Experiences with Academic Performance among Medical Students - Attili Venkata Narasimha Satya Padmaja; Abdul Salaam Mohammed; Donthu Raj Kiran (Journal of Psychiatry Spectrum)
Introduction: Trauma is an intense feeling of stress and unhappiness. This can include experiences such as physical abuse, neglect, assault, or betrayal. Trauma during childhood can have far-reaching effects on a child’s emotional development, attachment style, and belief system. Exposure to childhood trauma, as measured by adverse childhood experiences (ACEs), is associated with an increased risk of mental health challenges. Academic performance comprises a wide range of factors, and it is influenced by a combination of personal attributes, study habits, and external factors. Trauma, particularly in childhood, can have profound and long-lasting effects on a student’s ability to learn and succeed. Materials and Methods: It is a cross-sectional study of 400 medical graduates with a duration of 4 months. A sociodemographic detail questionnaire, ACE-IQ, and Academic Performance Scale (APS) were used. Statistical analysis was done using the R language. Results: Different variables of ACE scores are measured among medical graduates with a mean age of 21.7 years. There was a mild association between age (P = 0.001) and gender (P = 0.015) with academic performance. The abuse and family domain of ACE also had a significant association with educational level (P = 0.016 and 0.004, respectively). There is no significant association between overall ACE domains and APS scores. There was a significant association between academic behavior and performance with P < 0.001. Conclusion: The present study concludes that there is no association between ACE and academic performance among medical students.